Modern surgical strategies for perianal Crohn's disease - Zabot, Gilmara Pandolfo (2020)
One of the most challenging phenotypes of Crohn's disease is perianal fistulizing disease (PFCD). It occurs in up to 50% of the patients who also have symptoms in other parts of the gastrointestinal tract, and in 5% of the cases it occurs as the first manifestation. It is associated with severe symptoms, such as pain, fecal incontinence, and a significant reduction in quality of life. The presence of perianal disease in conjunction with Crohn's disease portends a significantly worse disease course. These patients require close monitoring to identify those at risk of worsening disease, suboptimal biological drug levels, and signs of developing neoplasm. The last 2 decades have seen significant advancements in the management of PFCD. More recently, newer biologics, cell-based therapies, and novel surgical techniques have been introduced in the hope of improved outcomes. However, in refractory cases, many patients face the decision of having a stoma made and/or a proctectomy performed. In this review, we describe modern surgical management and the most recent advances in the management of complex PFCD, which will likely impact clinical practice.